Morphological changes in the pons and cerebellum during the first two weeks in term infants with pontine and cerebellar injury and profound neonatal asphyxia. (August 2022) - Hayakawa, Katsumi; Tanda, Koichi; Nishimura, Akira; Kinoshita, Daisuke; Nishimoto, Masakazu; Kizaki, Zenro; Ohno, Koji
Background: The morphological changes in the pons and cerebellum of neonates experiencing profound asphyxia in the early period of life remain to be clarified. Purpose: To assess the changes in the size of the pons and cerebellum during the first two weeks of life in term neonates with pontine and cerebellar injury caused by hypoxic-ischemic encephalopathy in comparison with a control group. Material and Methods: Two groups were investigated: a group with pontine/cerebellar injury (PCI) (n = 10) demonstrated by magnetic resonance imaging (MRI) diffusion-weighted imaging; and a control group without PCI – focal-multifocal white matter injury and a normal pattern (n = 24). The anteroposterior diameter (APD) and height of the pons and cerebellar vermis, and the transverse width of the cerebellum were measured twice in the first and second weeks of life. Differences between the groups were analyzed statistically using paired and unpaired Student's t-test at a significance level of P < 0.05. Results: In the PCI group, the pontine APD and cerebellar vermian height were significantly decreased in the second week. An increase of pons and cerebellar size was evident during the first two weeks of life in the control groups. Conclusion: Infants with PCI and profound asphyxia show rapid decreases in pontine APD and cerebellar vermian height within the first two weeks of life.